The Alzheimer's Disease-Associated R47H Variant of TREM2 Has an Altered Glycosylation Pattern and Protein Stability - Park, Ji-Seon; Ji, In Jung; Kim, Dong-Hou; An, Hyun Joo; Yoon, Seung-Yong (Frontiers in Neuroscience, 2017)
The R47H coding variant of the triggering receptor expressed on myeloid cells-2 (TREM2) increases the risk of Alzheimer’s disease (AD) similar to apolipoprotein E4. TREM2 R47H has recently been shown to have impaired binding to damage-associated lipid or apolipoprotein ligands. However, it is not known how this R47H variant affects the biochemical characteristics of TREM2 and alters the pathogenesis of AD. We previously reported that TREM2-R47H has a slightly different glycosylation pattern from wild-type. A more detailed characterization in our present study confirms that TREM2 R47H has an altered glycosylation pattern and reduced stability. TREM2 R47H shows different glycosylation profiles from analysis using monensin or kifunensine treatment which were confirmed by mass spectrometry. The solubility of TREM2 R47H and its cleaved products such as intracellular domain (ICD) is also decreased, increasing its proteasomal and lysosomal degradation. The different biochemical characteristics of TREM2 R47H, including glycosylation, solubility and processing, may offer insights into a future therapeutic strategy for AD.